(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Wind power is the most developed of all renewable energy sources in positions of commercial growth. This energy source is appealing since it is both renewable and readily available. Wind energy development will result in land use changes and changes to landscape settings, all of which will have an influence on living space, biological systems, and regional earth surface systems, including noise pollution, greenhouse gas emissions, bird and bat deaths, and surface temperature. Wind power is being additional extensively employed as a sources of renewable energy across the globe. Wind energy development may have unanticipated environmental consequences. This study gives analysis to enhance comprehend the positive as well as negative impacts of the environment. As a consequence, a better knowledge of the environmental and economic implications of any one energy source necessitates a better considerate of how that energy source relocates or is displaced by other energy sources, as well as a better awareness of all other possible energy sources.